Modeling and nonlinear vibration characteristics analysis of symmetrically 3-layer composite thin circular cylindrical shells with arbitrary boundary conditions. (September 2019) - Li, Chaofeng; Zhong, Bingfu; Shen, Zengchuang; Zhang, Jinrui
Abstract: Considering the large-deformation hypothesis, the modeling and nonlinear vibration characteristics of symmetrically 3-layer composite thin circular cylindrical shells with arbitrary boundary conditions are analyzed by applying four sets of artificial springs. Firstly, by employing a set of orthogonal polynomials and trigonometric functions, the energy equations of the shells are derived with Donnell's nonlinear thin-shell theory. Then, the arbitrary boundary conditions are simulated by imposing the equivalent elastic constraint to obtain the potential energy of the edges of the shell, which can be universally applicable to all classical boundary conditions. The vibration equation is obtained by using the Lagrange equation method. In order to obtain correct numerical results, several comparisons of linear and nonlinear results are carried out to validate the approach method in the present study; meanwhile, the calculation convergence is checked. At last, the influence of boundary conditions, geometric parameters, symmetrical lamination schemes and damping coefficients on the nonlinear amplitude-frequency characteristics of symmetrically 3-layer composite thin circular cylindrical shells are investigated. The numerical results indicate that the present method is powerful to calculate the nonlinear vibration response characteristics of symmetrically 3-layer composite circular cylindrical thin shells subjected to various boundary conditions. Highlights: A new model of a 3-layer cylindrical shell with geometrical nonlinearity and arbitrary boundary conditions is presented. The nonlinear items' simplification principle is investigated for saving the computation time. The effect of arbitrary boundary conditions on the nonlinear vibration characteristics of the shell is analyzed. The nonlinear characteristics are analyzed for the geometric parameters and the lamination schemes.